Development and validation of a predictive model and tool for functional recovery in patients after postero-lateral interbody fusion - Shuai Zhou; Zhenbang Yang; Wei Zhang; Shihang Liu; Qian Xiao; Guangzhao Hou; Rui Chen; Nuoman Han; Jiao Guo; Miao Liang; Qi Zhang; Yingze Zhang; et al. (Journal of Orthopaedic Surgery and Research)
Abstract Objective The postoperative recovery of patients with lumbar disc herniation (LDH) requires further study. This study aimed to establish and validate a predictive model for functional recovery in patients with LDH and explore associated risk factors. Method Patients with LDH undergoing PLIF admitted from January 1, 2018 to December 31, 2022 were included, and patient data were prospectively collected through follow-up. The training and validation cohorts were randomly assigned in a 7:3 ratio. To pool data variables LASSO regression was used. The pooled variables were subsequently included in binary logistic regression analyses, construct risk prediction models, and plot nomograms. Additionally, recovery prediction models and interactive web page calculators were developed using R Shiny. Results Overall, 1,097 patients with LDH following PLIF were included in this study. Regarding patients’ economic and functional scores, 927 (84.5%) received excellent scores. Key indicators significantly were screened. Multivariate analysis showed that age, season, occupation, HDL-C, smoking, weekly exercise time, and osteoporosis were independent risk factors for postoperative recovery. The C-index of the model was 0.776 (95% CI: 0.7312–0.8208) and 0.804 (95% CI: 0.7408–0.8673) for the training and validation cohorts, respectively. The H–L test showed good fitting of the model (all P > 0.05). The DCA curve showed the best clinical efficacy when the threshold probability was in the ranges of 0–0.71 and 0.79–0.84. The interactive web calculator is accessed at https://postoperativerecoveryofldh.shinyapps.io/DynNomapp/ . Conclusion The predictive tools derived from this study can provide realistic and personalized expectations of postoperative outcomes for patients undergoing lumbar spine surgery.